Relationship Between Parenting Styles and Personality in Older Spanish Adolescents - Celia Cuadri; Joan García-Perales; Isabel Martínez; Feliciano Henriques Veiga (Behavioral Sciences)
Adolescence is a critical period for identity formation and psychological adjustment, where parenting styles play a fundamental role in shaping socialization and emotional development. The present study analyzed the relationships of parenting styles with the Big Five personality traits (extraversion, agreeableness, conscientiousness, emotional stability, and intellect), self-esteem, and life satisfaction in older Spanish adolescents. A sample of 366 Spanish university students (69.1% girls and 30.9% boys) aged 18 and 19 years completed measures assessing parenting styles, personality traits, self-esteem, and life satisfaction. Data analysis involved a multivariate approach, considering the four parenting styles as independent variables. The results of the MANOVA test indicate that adolescents raised with indulgent and authoritative parenting exhibit significantly higher levels of extraversion, agreeableness, conscientiousness, emotional stability, self-esteem, and life satisfaction compared to those raised with neglectful or authoritarian parenting. These findings highlight the influence of parenting styles not only on adolescent well-being, but also on personality development.